Clinical Epigenetics - Rots, Marianne; Altucci, Lucia
Clinical Epigenetics is an open access, peer-reviewed journal that encompasses all aspects of epigenetic principles and mechanisms in relation to human disease, diagnosis and therapy. Clinical trials and research in disease model organisms are particularly welcome.